The Development of DNA Based Methods for the Reliable and Efficient Identification of Nicotiana tabacum in Tobacco and Its Derived Products - Sukumar Biswas; Wei Fan; Rong Li; Sifan Li; Wenli Ping; Shujun Li; Alexandra Naumova; Tamara Peelen; Esther Kok; Zheng Yuan; Dabing Zhang; Jianxin Shi (International Journal of Analytical Chemistry)
Reliable methods are needed to detect the presence of tobacco components in tobacco products to effectively control smuggling and classify tariff and excise in tobacco industry to control illegal tobacco trade. In this study, two sensitive and specific DNA based methods, one quantitative real-time PCR (qPCR) assay and the other loop-mediated isothermal amplification (LAMP) assay, were developed for the reliable and efficient detection of the presence of tobacco (Nicotiana tabacum) in various tobacco samples and commodities. Both assays targeted the same sequence of the uridine 5′-monophosphate synthase (UMPS), and their specificities and sensitivities were determined with various plant materials. Both qPCR and LAMP methods were reliable and accurate in the rapid detection of tobacco components in various practical samples, including customs samples, reconstituted tobacco samples, and locally purchased cigarettes, showing high potential for their application in tobacco identification, particularly in the special cases where the morphology or chemical compositions of tobacco have been disrupted. Therefore, combining both methods would facilitate not only the detection of tobacco smuggling control, but also the detection of tariff classification and of excise.